Idiosyncrasies of Physical Vapor Deposition Processes from Various Knudsen Cells for Quinacridone Thin Film Growth on Silicon Dioxide - Scherwitzl, Boris (J Phys Chem C Nanomater Interfaces, 2015)
[Image: see text] Thin films of quinacridone deposited by physical vapor deposition on silicon dioxide were investigated by thermal desorption spectroscopy (TDS), mass spectrometry (MS), atomic force microscopy (AFM), specular and grazing incidence X-ray diffraction (XRD, GIXD), and Raman spectroscopy. Using a stainless steel Knudsen cell did not allow the preparation of a pure quinacridone film. TDS and MS unambiguously showed that in addition to quinacridone, desorbing at about 500 K (γ-peak), significant amounts of indigo desorbed at about 420 K (β-peak). The existence of these two species on the surface was verified by XRD, GIXD, and Raman spectroscopy. The latter spectroscopies revealed that additional species are contained in the films, not detected by TDS. In the film mainly composed of indigo a species was identified which we tentatively attribute to carbazole. The film consisting of mainly quinacridone contained in addition p-sexiphenyl. The reason for the various decomposition species effusing from the metal Knudsen cell is the comparably high sublimation temperature of the hydrogen bonded quinacridone. With special experimental methods and by using glass Knudsen-type cells we were able to prepare films which exclusively consist of molecules either corresponding to the β-peak or the γ-peak. These findings are of relevance for choosing the proper deposition techniques in the preparation of quinacridone films in the context of organic electronic devices.